Conceptual model to reduce non-contributory time based on Lean tools in the construction industry in Peru - Cabrera, Olenka (2022)
The construction sector in Peru is growing and is one of the most important, representing 19% of GDP. However, currently, in the construction industry, there is a high rate of non-contributory time, that is, the activities carried out during the construction process have a large percentage of time dedicated to activities that do not add value and lead to losses. This research attempts to reduce the high rate of non-contributory time (NCT) in building maintenance services in a Peruvian company in the construction sector. To achieve this, a conceptual model at the managerial level based on Lean tools such as Kanban, 5S, TPM was proposed.